Susceptibility of European Agrilus beetle species to the biocontrol agents of Emerald Ash Borer in the laboratory - Katy Reed; Freya Cole; Neil Audsley; Anastasia Uglow; Rachel Down; Kerry Barnard; Daegan Inward (Biological Control)
The emerald ash borer (EAB, Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) is devastating ash trees in its invaded range of North America and spreading rapidly towards Western Europe from European Russia and Ukraine. To allow a rapid response when the beetle is detected, slow its spread and protect trees as part of a wider integrated pest management programme, pre-emptive biological control strategies that are suitable for Great Britain and the rest of Europe must urgently be developed. Three classical hymenopteran biological control agents have been mass-reared and released within North America to control EAB: the egg parasitoid Oobius agrili Zhang and Huang (Hymenoptera: Encyrtidae), and the larval parasitoids Tetrastichus planipennisi and Spathius galinae Belokobylskij & Strazanac (Hymenoptera: Braconidae). This study presents data on the risk these parasitoid wasps might pose to British Agrilus beetles. “No-choice” laboratory assays tested the susceptibility of A. biguttatus Fabricus eggs and larvae and A. sulcicollis Lacordaire and A. convexicollis Redtenbacher eggs to the parasitoids. Oobius agrili, T. planipennisi and S. galinae all attacked A. biguttatus, and offspring were produced. Oobius agrili also attacked the eggs of A. convexicollis, but not A. sulcicollis. This study is the first to show parasitism of a non-target species by T. planipennisi. Further work is needed to fully assess the non-target risk of these parasitoids for release using more ecologically relevant tests, such as ‘choice’, semi-field and chemical ecology assays on the attacked Agrilus species.